P04.14 Loss of oligodendroglial features at recurrence in five diffuse low-grade glioma patients treated with repeated surgery. (6th September 2019) - Darlix, A; Duffau, H; Rigau, V; Gozé, C
Abstract: BACKGROUND: Diffuse low-grade gliomas (DLGG) are characterized by a continuous growth and an unavoidable anaplastic transformation. IDH mutation and 1p19q codeletion have been integrated to the 2016 WHO classification to define the oligodendroglioma entity. Whenever feasible, neurosurgical resection is the first treatment option. At recurrence, a second surgical resection is proposed in selected cases. The consistency of molecular patterns (IDH mutation, 1p19q codeletion) at recurrence has been poorly studied in DLGG. MATERIAL AND METHODS: We conducted a retrospective study on consecutive DLGG patients treated at our institution with repeated surgery (2006–2017). Clinical and biological data were collected for both the initial and subsequent surgery. Additional immunohistochemistry (including tumor morphology, ATRX and p53) and genetic analyses (TERT promoter mutation, CIC mutation, CGHa) were also performed on tumors with joint loss of IDH mutation and of 1p19q codeletion at recurrence. RESULTS: A total of 71 patients were identified. Analyses were carried out on 56 patients (molecular data missing: n=15). Nine patients (16.1%) presented with a loss of their IDH mutation at second surgery. Five of them (8.9%) had an additional loss of their 1p19q codeletion. These five cases (3 men, median age 36.6 years) were all treated with surgery as the first oncological treatment. The first surgery revealed in all cases tumors with morphological oligodendroglial features, IDH mutation and 1p19q codeletion. Further molecular analysis strengthened the diagnosis of oligodendroglioma (TERT promoter and CIC mutations, no ATRX loss, no expression of p53). Four patients were followed-up after the first surgery; one patient received Temozolomide 14 months later due to FLAIR tumor volume growth. Because of the regrowth of the residual FLAIR tumor volume, a second surgery was performed in all patients, after a median time of 38.9 months. The morphological oligodendroglial features were lost, and the genetic analyses revealed in all cases no IDH mutation, no 1p19q codeletion, no ATRX loss and no expression of p53. No evidence of anaplasia was found histologically or by CGHa analysis in these recurrent tumors. CONCLUSION: We describe five DLGG patients with a shared histo-molecular evolution characterized by the loss of the initial IDH mutation and of oligodendroglial features at second surgery. While rare, this possible evolution must be acknowledged as it can impact the subsequent therapeutic strategy. This observation is the first of a loss of founder alterations in DLGG genesis (i.e. IDH mutation and 1p19q codeletion); the involved mechanism likely differs from the previously described oligoclonal selection caused by spontaneous tumor genetic drift and/or pressure of chemotherapy, and could be linked with the Darwinian selection of a subpopulation of tumor cells after the first surgery.